Corticosteroids to safely reduce neonatal respiratory morbidity after late preterm and term planned caesarean section birth? A randomised placebo-controlled feasibility study. Issue 9 (7th September 2022) - CHAN, Johanna; Mackay, Laura; Bloomfield, Frank; Crowther, Caroline; Lee, Arier; Morris, Jonathan M; Hay, Rebecca; Oakes-ter Bals, Mariska; Thurnell, Christopher; De Jong, Phoebe; Carlsen, Victoria; Williams, Tracey; et al.
Abstract : Objectives: To assess the feasibility of conducting a randomised placebo-controlled trial of corticosteroids prior to planned caesarean section from 35 +0 to 39 +6 weeks. Design: A triple-blind, placebo-controlled, parallel, trial randomised at the participant level (1:1 ratio). Additional feasibility data obtained by questionnaires from trial participants and women who declined trial participation, and focus groups with local site researchers and clinicians. Setting: Three obstetric units in New Zealand including tertiary and secondary care; public and private care, and research active and non-active units. Participants: Women undergoing a planned caesarean section from 35 +0 to 39 +6 weeks; local site researchers and clinicians. Interventions: Two doses of 11.4 mg betamethasone or saline placebo. Questionnaires and focus group meetings. Primary and secondary outcome measures: Primary outcome: trial recruitment rate of eligible women. Secondary outcomes: trial recruitment by gestational age, site and delivery indication; proportion of babies who completed measurements of blood glucose concentrations as per protocol; overall incidence neonatal respiratory distress requiring >60 min of respiratory support; overall incidence of neonatal hypoglycaemia, and barriers and enablers to trial participation by participants, researchers and clinicians. Results: The recruitment rate was 8.9% (88/987) overall and 11.2% (88/789) for those approached about the trial. Neonatal blood glucose concentrations were measured as per protocol in 87/92 (94.6%) babies. For potential participants, key enablers to participation were contributing to research, a feeling of relevance and a good understanding; key barriers were a lack of understanding and concerns over safety. For researchers and clinicians, themes representing enablers and barriers included relevance, communication and awareness, influences on women's decision-making, resource challenges and trial process practicalities. Conclusions: Some women are willing to participate in a randomised placebo-controlled trial of corticosteroids prior to a planned caesarean section birth at late preterm and term gestations. Participation in such a trial can be enhanced.